Development possibilities of railway vocational education - Farkas, Attila; Filep, Roland; Dajnoki, Krisztina (Studia Mundi – Economica, 2023)
The safe operation of the railway requires that the workers receive the theoretical and practical training with which reliable operation can actually be carried out. The purpose of the study is to investigate the deficits of railway vocational education. In the course of the research, we looked for an answer to the question that, in addition to revealing the strengths/weaknesses, what are the opportunities/threats, the knowledge of which can improve and improve the quality of education. We conducted individual and focus group interviews, based on the results of which we prepared a SWOT analysis. We found that it appears as a strength that most of the instructors are dedicated and have innovative ideas. The training system, on the other hand, is outdated and the curriculum needs to be standardized. The organizational units see many opportunities to improve the situation, such as strengthening input and output requirements, making education more practical, and implementing more innovative solutions using Education 4.0. Organizational units can also help each other by sharing best practices. In addition to standardizing and modernizing the curriculum, we recommend organizing a joint forum that can help in sharing knowledge.